From Tokenism to Partnership: Community Participation in Managing Batu Dua Paragliding Sport Tourism, Indonesia - Dally Nur Arif; Irena Novarlia (Darul Yasin Al Sys, 2026)
Batu Dua is a rural paragliding destination in Linggajaya Village, Sumedang Regency, Indonesia, where international event visibility contrasts with unresolved questions concerning community influence over destination decision-making. This study aimed to evaluate the forms of community participation in destination management and identify the highest level of authority demonstrated in practice. A qualitative single-case study design was employed, combining semi-structured interviews with four role-based informants, field observations, and document analysis. Interview data were coded using Arnstein’s eight-rung Ladder of Citizen Participation and validated through source and method triangulation. Informant corroboration percentages were calculated descriptively by dividing the number of informants providing evidence for each rung by four and were not interpreted as population estimates. The findings reveal a hybrid participation profile. All informants reported government-led information provision, capacity-building activities, and operational collaboration; three reported two-way communication and consultation; two provided evidence of placation through community representation; and none reported delegated power or citizen control. Community members participated in parking management, food and beverage services, promotion, event support, and facility maintenance, while strategic decision-making authority remained concentrated among formal destination managers and government actors. Partnership therefore constituted the highest observed level of participation, although it did not represent comprehensive citizen power. The study concludes that community involvement at Batu Dua remains primarily operational rather than authority-based. These findings extend understanding of participation in rural sport tourism governance and indicate that progression toward formal co-management requires explicit decision-making rights, transparent benefit-sharing mechanisms, accountable community representation, and participatory monitoring.